The Relationship Between Physical Fitness and Reproductive Health in Adolescents Among FIKK UNM Students (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aimed to examine the relationship between physical fitness and reproductive health among female students at the Faculty of Sports and Health Sciences (FIKK) Universitas Negeri Makassar (UNM), addressing the gap in empirical evidence for university populations specifically trained in sports and health sciences. A quantitative correlational design was conducted involving 120 female undergraduate students aged 18–24 years, selected using purposive sampling. Physical fitness was assessed using standardized field tests, including cardiovascular endurance (1,600 m run), muscular endurance (sit-ups), and flexibility (sit-and-reach). Reproductive health was measured via a validated structured questionnaire covering menstrual regularity, menstrual discomfort, and hygiene practices. Data were analyzed using descriptive statistics and Pearson’s correlation coefficients, with significance set at p < 0.05. Descriptive analysis showed that 40% of participants had below-average fitness. Regarding reproductive health, 35% reported irregular menstrual cycles, 42% experienced moderate to severe menstrual discomfort, and 43% had suboptimal hygiene practices. Correlation analysis indicated significant relationships between physical fitness and reproductive health: cardiovascular endurance had a moderate positive correlation with menstrual regularity (r = 0.342, p = .001) and a moderate negative correlation with menstrual discomfort (r = -0.311, p = .002). Muscular endurance and flexibility also demonstrated significant positive and negative correlations with reproductive health indicators, although to a lesser extent. The findings suggest that higher physical fitness, particularly cardiovascular and muscular endurance, may improve menstrual regularity, reduce discomfort, and support optimal hygiene practices. Integrating structured physical activity programs in campus health initiatives could enhance reproductive well-being among female students. The study includes three tables summarizing descriptive statistics and correlation analyses, and employed validated field tests and structured questionnaires to ensure empirical rigor.